Teaching Arabic-English Translation in the University of Ilorin Nigeria: Any Challenges? - Adebisi, Aliy Abdulwahid; Mukadam, Abdur-Rasheed Mahmoud (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2020)
The practice of translation generally presents a lot of difficulties and issues. The process becomes more complicated when dealing with teaching translation especially in higher institutions. This study examines the dynamics of teaching the practice of translation taking the example of University of Ilorin. Thus, the study investigates the significance of translation teaching, teaching materials, techniques and teaching methods. This is done with a view to uncovering the challenges encountered by concerned lecturers teaching translation courses at the University of Ilorin. In this study, a descriptive approach was utilized in identifying the problems associated with teaching translation. With this method, questionnaires (containing 11 questions open ended) were administered. This research reveals the challenges encountered and proposes some practical procedures to resolve them. The outcomes and recommendations also proffer new vistas and possible solutions which would assist facilitators and other stakeholders to improve the way translation is taught in the University.